The Effect of Obesity on Pulmonary Function among Healthy Non-smoking Adults: The Effect of Obesity on Pulmonary Function among Healthy Non-smoking Adults - Nachimuthu, Kanchana (International Journal of Pharmaceutical & Biological Archive, 2020)
Background: Obesity is a chronic disease characterized by the excessive accumulation of body fat which is associated with comorbidities. It is a growing health issue worldwide. Obesity is known to have significant effects on respiratory function and obese patients commonly report respiratory complaints requiring pulmonary function tests. Objectives: The objectives of the study were to determine the effects of obesity on pulmonary function in overweight and obese adults who were non-smokers and did not have any respiratory diseases. Materials and Methods: This cross-sectional study was carried out among 181 healthy adults of both sexes between 20 and 60 years, those attended master health check-up and medicine outpatient department. The study participants were divided into three body mass index (BMI) groups according to the WHO BMI classification. Forced vital capacity in liters (FVC), forced expiratory volume in the first second in liters (FEV1), FVC/FEV1, peak expiratory flow rate in liter/min (PEFR), and forced expiratory flow (FEF)25â€“75% were recorded. These three BMI groups were compared using one-way ANOVA, correlation was assessed by Pearsonâ€™s â€œr.â€ Linear regression analysis was applied. Results: Significant differences in lung volumes were found in three BMI groups. Obese and overweight subjects had significantly lower FVC, FEV1, FEF25%â€“75%, and PEFR (P < 0.0001) as compared to normal weight subjects. However, there was no statistically significant difference found in FEV1/FVC ratio. There were significant linear relationships between obesity and pulmonary function. BMI had significant negative linear association at the level of P < 0.001 with FVC% (r = âˆ’0.355), FEV1% (r = âˆ’0.361), FEF25%â€“75% (âˆ’0.432), and PEFR (r = âˆ’0.501). FEV1/FVC ratio was negatively correlated, but statistically not significant. Conclusion: BMI has a detrimental effect on pulmonary functions in overweight and obese subjects. Reduction in FVC and FEV1 was the most representative findings among the overweight and obese subjects, suggesting the presence of a restrictive respiratory pattern associated with obesity. It might be due to decrease in lung and chest wall compliance and increase in work of breathing.